Emblem Gestures Improve Perception and Evaluation of Non-native Speech - Billot-Vasquez, Kiana; Lian, Zhongwen; Hirata, Yukari; Kelly, Spencer D. (Frontiers in Psychology, 2020)
Traditionally, much of the attention on the communicative effects of non-native accent has focused on the accent itself rather than how it functions within a more natural context. The present study explores how the bodily context of co-speech emblematic gestures affects perceptual and social evaluation of non-native accent. In two experiments in two different languages, Mandarin and Japanese, we filmed learners performing a short utterance in three different within-subjects conditions: speech alone, culturally familiar gesture and culturally unfamiliar gesture. Native Mandarin speakers watched videos of foreign-accented Mandarin speakers (Experiment 1), and native Japanese participants watched videos of foreign-accented Japanese speakers (Experiment 2). Following each video, native language speakers were asked a set of questions targeting speech perception and social impressions of the learners. Results from both experiments demonstrate that familiar—and occasionally unfamiliar—emblems facilitated speech perception and enhanced social evaluations compared to the speech alone baseline. The variability in our findings suggests that gesture may serve varied functions in the perception and evaluation of non-native accent.